Analisa Kerusakan Alternator Pada Engine C6.4 Excavator 320D Caterpillar - Abdul Muis; Mangkona Mangkona; Darma Aviva; Faisyal Faisyal (Politeknik Negeri Samarinda, 2021)
The alternator plays an important role in supplying the battery, lighting accessories and turning on the unit at the time of starting, therefore it needs more attention to it. Damage can occur at any time, and finding the problem with it presents its own challenges. Equipment such as a multimeter/avometer is needed to analyze the damage. Visual inspection, testing, and measurement are steps that must be taken to be able to find damage that occurs in the alternator. The charging system can be disrupted if there is an operational problem with the alternator component. This can be identified through an examination of the damage that occurred. Maintenance/maintenance on the components of the charging system must be carried out periodically so that the electricity supply remains optimal.